1998
DOI: 10.1377/hlthaff.17.5.208
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of Maternity-Stay Legislation On ‘Drive-Through Deliveries’

Abstract: We evaluate the change in length-of-stay and charges for vaginal and cesarean deliveries before and after the implementation of a law establishing a minimum maternity stay in Maryland. Using discharge abstract data collected by the Maryland Health Services Cost Review Commission, we find that after the law was enacted, Maryland's average length-of-stay and average charges for both types of deliveries increased, but the increase in charges was less than the cost of an average hospital day. Multivariate analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 1 publication
2
22
0
Order By: Relevance
“…These results are consistent with previous research that has also examined the LOS effects of postpartum legislation in other states. 6,9,11,[18][19][20] The current study adds to this literature by examining how the effects of the postpartum legislation on LOS varied with demographics, delivery type, and deliveryand pregnancy-related complications. It is important to examine these differential effects to evaluate whether the legislation had a greater impact on LOS for infants who were at greater risk of adverse outcomes because of early discharge.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous research that has also examined the LOS effects of postpartum legislation in other states. 6,9,11,[18][19][20] The current study adds to this literature by examining how the effects of the postpartum legislation on LOS varied with demographics, delivery type, and deliveryand pregnancy-related complications. It is important to examine these differential effects to evaluate whether the legislation had a greater impact on LOS for infants who were at greater risk of adverse outcomes because of early discharge.…”
Section: Discussionmentioning
confidence: 99%
“…To calculate the lower-and upper-bound cost estimates, we relied on data from surveys, 15,16 a randomized controlled trial, 17 and administrative records. 6,13,18 All costs were expressed in 2000 US dollars using the medical care component of the Consumer Price Index. We did not discount costs because almost all costs attributable to increased postpartum LOS are incurred within the first few weeks after birth.…”
Section: Costsmentioning
confidence: 99%
“…Two studies of costs concluded that increasing postpartum LOS is associated with additional hospital costs of $20 to $23 per hour (in 2000 dollars). 13,14 Thus, according to these studies, extending the average postpartum stay by 12 hours would cost a hospital between $240 and $276 per birth. These estimates seem to be too high for hospitals where longer stays do not affect hospital capacity.…”
mentioning
confidence: 99%
“…Against this background, this paper attempts to identify risk factors for short-stay, medium-stay and long-stay subgroups of patients, and analyzes LOS as an indicator of the pressure on inpatient treatment, with a view to enhancing standardization of the curative healthcare delivery system in India. From both the physical and mental health perspectives of patients, the shorter the recovery time (in terms of shorter LOS), the more effective is the curative treatment [4][5][6].…”
Section: Introductionmentioning
confidence: 99%